2015
DOI: 10.1080/15548627.2015.1067359
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase inhibition by WP1130 leads to ULK1 aggregation and blockade of autophagy

Abstract: Autophagy represents an intracellular degradation process which is involved in both regular cell homeostasis and disease settings. In recent years, the molecular machinery governing this process has been elucidated. The ULK1 kinase complex consisting of the serine/threonine protein kinase ULK1 and the adapter proteins ATG13, RB1CC1, and ATG101, is centrally involved in the regulation of autophagy initiation. This complex is in turn regulated by the activity of different nutrient- or energy-sensing kinases, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 39 publications
3
34
1
Order By: Relevance
“…To characterize the ULK1 puncta observed in USP1depleted cells, we verified their colocalization/interaction with the ubiquitin-binding receptor protein SQSTM1 both by immunofluorescence analysis and immunoprecipitation experiments. As previously shown for WIP1130-dependent GFP-ULK1 aggresomes [20], endogenous ULK1 partly colocalized with SQSTM1 dots (Figure 5(a,c)). Notably, SQSTM1 dots were more abundant in USP1-depleted cells ( Figure 5(a, b)).…”
Section: Usp1 Modulates Ulk1 Compartmentalization In Mammalian Cellssupporting
confidence: 84%
See 4 more Smart Citations
“…To characterize the ULK1 puncta observed in USP1depleted cells, we verified their colocalization/interaction with the ubiquitin-binding receptor protein SQSTM1 both by immunofluorescence analysis and immunoprecipitation experiments. As previously shown for WIP1130-dependent GFP-ULK1 aggresomes [20], endogenous ULK1 partly colocalized with SQSTM1 dots (Figure 5(a,c)). Notably, SQSTM1 dots were more abundant in USP1-depleted cells ( Figure 5(a, b)).…”
Section: Usp1 Modulates Ulk1 Compartmentalization In Mammalian Cellssupporting
confidence: 84%
“…It has been shown that deubiquitinase inhibition by WP1130 reduce the protein level of ULK1 in the Triton X-100 soluble fraction of mammalian cell extracts [20]. In confirmation of this study, USP1 depletion using siRNA, was coupled to a reduction of total ULK1 and ULK1 p-Ser555 in the soluble fraction of U2OS, HEK293, and MCF10AT cells ( Figure 1(df)).…”
Section: Usp1 Modulates Ulk1 Compartmentalization In Mammalian Cellssupporting
confidence: 83%
See 3 more Smart Citations